Les impacts humains des changements organisationnels autour des TIC - Robert Picard (Perspectives Interdisciplinaires sur le Travail et la Santé)
Many organizational changes are related to (or initiated by) the introduction of information and communication technology (ICT) tools.The size of the systems implemented in large organizations, their external nature vis-à-vis the company’s practices (Enterprise Resource Planning) are rather new challenges, which are difficult for the actors to tackle. In fact, the jobs of data processing people as well as of professional users are often the most affected.Data processing people must revise their way of doing things, a change that is accompanied by a loss of autonomy and greater demands for cooperation and multidisciplinarity that they are not necessarily prepared for.Professional users may lose some historical guidelines, a change that is accompanied by a review of their practices, organizational changes, and changes in the work environment. They must sometimes develop new capacities, which may be costly for them, and some may even lose their jobs.These questions will be illustrated in two actual recent situations observed in a major service provider, for each of the populations.